Measuring nonuniform web tension for roll-to-roll manufacturing of flexible and printed electronics. (11th August 2021) - Feng, Dan; Wagner, Ryan B; Raman, Arvind
Abstract: High-quality roll-to-roll (R2R) manufacturing for flexible and printed electronics often requires uniform web tension. Nonuniformity in web tension can lead to nonuniform performance of printed electronic devices across the width of the web, and excessive nonuniformity in web tension can lead to web wrinkling. Here we develop and test a noncontact resonance (NCR) method and a gentle contact stiffness mapping (GCSM) method for measuring the average web tension and its linear variation across the width of the web. The NCR method uses the lowest symmetric and anti-symmetric frequencies of a web with a closed-form expression to obtain its linearly varied tension. The closed-form expression includes the significant effects of air loading on web vibrations through accurate hydrodynamic functions. While the GCSM method is based on nonlinear regression of the contact stiffness on multiple locations of the web. Both methods are accurate, reliable, and inexpensive, and are compatible for a wide range of web properties, web path, web tension, measurement configurations, and environmental conditions. We cross-validate the two methods on a stationary test stand and in-line test the NCR method in two spans of a moving commercial R2R system. We measure up to 35.58% cross-span tension variation in that system, and both average tension and its linear variation can vary in different spans of the same R2R system. We expect the results presented in this article can improve quality control of R2R processes for flexible and printed electronics and maximize device yields.